Which Came First? Assessing Transactional Relationships Between Children’s Violent Media Use and ADHD-Related Behaviors - Beyens, Ine and Piotrowski, Jessica Taylor and Valkenburg, Patti M. (Communication Research, 2020)
This longitudinal study investigated transactional relationships between violent media use and attention-deficit/hyperactivity disorder (ADHD)–related behaviors among young children (ages 4-8 years). To investigate study hypotheses, we employed a random intercept cross-lagged panel model (RI-CLPM) using structural equation modeling with panel data from 890 children. Results provided evidence in support of a media selection process rather than media effects process, whereby an increase in a child’s ADHD-related behaviors predicted an increase in the child’s violent media use 1 year later. Results indicated that this longitudinal relationship was accounted for by within-child fluctuations over time rather than stable between-child differences. The findings highlight the importance of investigating transactional relationships as well as distinguishing between-person and within-person relationships.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE4NzgyMzAw